A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Where do adaptive shifts occur during invasion? A multidisciplinary approach to unravelling cold adaptation in a tropical ant species invading the Mediterranean area - Olivier Rey; Arnaud Estoup; Merav Vonshak; Anne Loiseau; Simon Blanchet; Luis Calcaterra; Lucila Chifflet; Jean‐Pierre Rossi; Gaël J. Kergoat; Julien Foucaud; Jérôme Orivel; Maurice Leponce; et al. (Ecology Letters, 2012)
Evolution may improve the invasiveness of populations, but it often remains unclear whether key adaptation events occur after introduction into the recipient habitat (i.e. post‐introduction adaptation scenario), or before introduction within the native range (i.e. prior‐adaptation scenario) or at a primary site of invasion (i.e. bridgehead scenario). We used a multidisciplinary approach to determine which of these three scenarios underlies the invasion of the tropical ant Wasmannia auropunctata in a Mediterranean region (i.e. Israel). Species distribution models ( SDM ), phylogeographical analyses at a broad geographical scale and laboratory experiments on appropriate native and invasive populations indicated that Israeli populations followed an invasion scenario in which adaptation to cold occurred at the southern limit of the native range before dispersal to Israel. We discuss the usefulness of combining SDM , genetic and experimental approaches for unambiguous determination of eco‐evolutionary invasion scenarios.

Interspecific displacement mechanisms by the invasive little fire ant Wasmannia auropunctata - Merav Vonshak; Tamar Dayan; Abraham Hefetz (Biological Invasions, 2012)

The little fire ant Wasmannia auropunctata: a new invasive species in the Middle East and its impact on the local arthropod fauna - Merav Vonshak; Tamar Dayan; Armin Ionescu-Hirsh; Amnon Freidberg; Abraham Hefetz (Biological Invasions, 2010)

The interplay between genetic and environmental effects on colony insularity in the clonal invasive little fire ant Wasmannia auropunctata - Merav Vonshak; Tamar Dayan; Julien Foucaud; Arnaud Estoup; Abraham Hefetz (Behavioral Ecology and Sociobiology, 2009)